'From presence to participation – the role of the juror reimagined.'. Issue 2 (3rd July 2017) - Scott, Jenny
ABSTRACT: This article raises new questions about the meaning of juror participation in a criminal trial. Through an interdisciplinary exploration I not only theorize the position and potentiality of the jury, but I also reflect on the process of working with a theatre director to create work which is both academic research and public theatre performance in equal measure. I challenge the reader to reconsider the current assumptions which equate juror presence in the courtroom to their participation in the trial by drawing on participatory techniques found in Augusto Boal's Forum Theatre and my current collaboration with site-specific theatre company, Grid Iron.